Benign and malignant collision tumors of melanocytic skin lesions with hemangioma: Dermoscopic and reflectance confocal microscopy features. Issue 2 (31st January 2018) - Tognetti, L.; Cinotti, E.; Perrot, J.L.; Campoli, M.; Fimiani, M.; Rubegni, P.
Abstract: Background: Though the combination/collision of nevi or lentigo simplex and hemangiomas is frequent, the malignant collision tumor melanoma‐hemangioma is exceptional and can sometime clinically simulate a benign collision. To date, a series of collision tumors of hemangiomas associated with either benign or malignant melanocytic skin lesions (MSL) has yet to be studied by non‐invasive imaging and clinico‐pathologic correlates. Methods: We present 10 cases of patients with collision tumors of hemangioma with different MSL including: 2 in situ lentigo‐maligna melanoma, 1 invasive melanoma, 5 melanocytic nevi, and 2 lentigo simplex. The clinical aspect along with the dermoscopic and reflectance confocal microscopy (RCM) features is described and compared with histopathologic findings. Results: Dermoscopic examination allows to recognize a dark ring in malignant collision melanoma‐hemangioma and a jelly ring sign in benign collision of nevi/lentigo simplex‐hemangioma. These peculiar features were confirmed by RCM and histopathologic findings. Conclusion: Two simple dermoscopic clues confirmed by RCM features can be proposed to help distinguish between benign and malignant collisions tumors.